PENGARUH LOCUS OF CONTROL, INTEGRITAS, DAN KOMUNKASI INTERPERSONAL TERHADAP KEPUASAN KERJA PNS DINAS PENDIDIKAN, PEMUDA, DAN OLAHRAGA KABUPATEN KARAWANG THE EFFECT OF LOCUS OF CONTROL, INTEGRITY, AND INTERPERSONAL COMMUNICATION ON PUBLIC SERVANT’ OB SA - NADEAK, BANUARA (Jurnal Politikom Indonesiana, 2017)
ABSTRACT The aim of this research is to obtain information related to the effect of locus of control, integrity, interpersonal communication on public servant’ job satisfaction of departement of education, yout and sports in karawang district. Survey was conducted in this research with 100 sample of public servants selected randomly. Data have been analyzed by path analysis. The findings of this research show that (1) locus of control effects directly on job satisfaction (2) integrity effects directly on job satisfaction and (3) interpersonal communication effects directly on job satisfaction (4) locus of control effects directly on interpersonal communication; and (5) integrity effects directly on interpersonal communication. Based on those findings it can be concluded that any concern toward locus of control, integrity, interpersonal communication should be put into strategic planning of human resources development in increasing job satisfaction of public servants of departement of education, yout and sport in karawang district. Keywords : locus of control, integrity, interpersonal communication, and job satisfaction.